ANALYSIS OF THE EFFECT OF COMPANY SIZE, AGE, GOVERNANCE, AND OPERATING COSTS ON THE FINANCIAL PERFORMANCE OF FINANCING COMPANIES IN INDONESIA - Budiyono; Harjum Muharram (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Conventional finance companies are an important part of the non-bank financial industry in Indonesia, which functions in financing investment, working capital, and public consumption. As a financial institution that supports national economic growth, its financial performance needs to be continuously analyzed and improved. This study aims to examine the effect of company size, company age, corporate governance, and operating costs on the financial performance of conventional finance companies in Indonesia. The method used in this study is a quantitative method using secondary data obtained from the annual financial reports of conventional financing companies registered with the Financial Services Authority (OJK) for the period 2019–2023. From a population of 179, 141 financing companies met the purposive sampling criteria, resulting in a total of 705 observations. After outlier trimming was carried out because there were indications of normality and heteroscedasticity problems, the final data analyzed were 495 observations. The analysis was carried out with SPSS 26.00 software using the multiple regression analysis method. The results of the study indicate that company size has a positive and significant effect on financial performance (ROA) (sig. 0.000; t-stat 3.713), company age has a significant positive effect on financial performance (ROA) (sig. 0.003; t-stat 2.953), corporate governance has a significant positive effect on ROA (sig. 0.007; t-stat 2.690), and operating costs have a negative effect on financial performance (ROA) (sig. 0.068; t-stat -1.832). The coefficient of determination (R² square) value of 0.109 indicates that the independent variables are able to explain 10.9% of the variation in financial performance of finance companies proxied by ROA. The implications of this study emphasize the importance for finance companies to expand their company scale and control operating costs strictly in order to improve financial performance. This study also opens up opportunities for further research to expand the scope of other factors, such as external macroeconomic factors that can affect the financial performance of finance companies in the future